THE WILL TO MEANING IN LOGOTHERAPY - Kadinov, Iliya (E-Journal VFU, 2025)
This article examines the psychological dimension of the will to meaning in Viktor Frankl’s logotherapy. It traces the derivation of the concept of "will to meaning" from philosophy and its application in logotherapy. The will to meaning is compared with the will to pleasure in Sigmund Freud’s psychoanalysis and the will to power in Alfred Adler’s individual psychology.